Azidoxanthone and azidofluorane-photoinitiated polymerizations of methyl methacrylate - Novikova, E.; Kolendo, A.; Syromyatnikov, V.; Prot, T.; Golec, K. (Polimery, 2022)
Novel organic azides were prepared, viz., derivatives of xanthone and fluorane (formulas I and II), and their photolysis initiated by radiation (X = 365 nm) was studied in ethanol and dimethylformamide (DMF) solutions in terms of IR and UV spectra (Scheme A, Figs. 1-4). A 15% methyl methacylate (MMA) solution in DMF was photopolymerized in the presence of the azides, benzoin and xanthone, and also in the bulk (to eliminate solvent effects) at 30šl°C in an argon atmosphere. The kinetics of the reaction was followed by dilatometry. The rate of polymerization of MMA photoinitiated with xanthone and fluorane azides was found to be higher than that run in the presence of xanthone and lower than that run in the presence of benzoin (Table 1, Fig. 5). Incorporation of a second azide group into the carbonyl photoinitiator (xanthone) resulted in higher reaction rates as compared with the rate observed in the presence of the monoazides. Discontinuation of irradiation was followed by the "dark" polymerization effect. The process was first accelerated and then decelerated. With xanthone or benzoin, no such effect was found to occur. The energy of activation of the "dark" polymerization with 2-azidoxanthone was estimated at 43 kJ/mol over 22-42°C. The durable effect of the "dark" polymerization and its temperature dependence were also observed in the bulk polymerization (Fig. 12). The aromatic azides containing no carbonyl group (e.g., azidoben-zene, p,p’-diazidobiphenyl, p,p’-diazidodiphenylmethane) failed to initiate photopolymerization under the present experimental conditions.